Generation of Design Ideas using EDOS-Touch. (4th March 2019) - Cheng, Yuan-Bang; Chang, Teng-Wen; Yang, Chuan-Kai
Abstract: In the digital era, the paper-based collage and mind-map have been gradually developed into digital forms. This study aims to develop a new digital collage tool called EDOS-Touch for helping novice designers (students) to generate design ideas through the design exploration. The authors propose two characteristics, i.e. intuitive manipulation and immersive experience; both are important to build a better digital collage tool. For evaluating its effectiveness, the authors conducted an experiment to answer two research questions. Eight subjects were selected from five groups of all participants involved; those in session 1 used EDOS-Touch and those in session 2 a paper-based collage. Quantitative results are presented, and significant observation notes and interview comments discussed. The conclusion reached is that EDOS-Touch provides novice designers with appropriate assistance in generating design ideas (like the paper-based collage), but is even better. The authors suggest that the multi-touch interface and big screen size are two important considerations.